2021
DOI: 10.3389/fpsyt.2021.759449
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in Children in the Context of COVID-19: Focus on Discharged Children

Abstract: Introduction: To date, the mental health consequences of children hospitalized with COVID-19 remain unclear. We aimed to assess mental health status in children in the context of COVID-19, with a focus on discharged children.Methods: We recruited discharged children who recovered from COVID-19 and healthy controls between July and September 2020 in Wuhan Children's Hospital. Post-traumatic stress disorder (PTSD), anxiety, depression, and sleep problems were assessed in these children using questionnaires. Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Over time, more attention has been paid to the psychological consequences of the SARS-CoV-2 infection. In accordance with previous data, which demonstrated an increased risk of depression in the patients recovered from COVID-19, our data show a very high of rate of anxiety and, especially, depression [ 24 , 25 , 26 ]. Of note, among our adolescents, 16.2% of the sample scored positive for suicidal or self-harm ideation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Over time, more attention has been paid to the psychological consequences of the SARS-CoV-2 infection. In accordance with previous data, which demonstrated an increased risk of depression in the patients recovered from COVID-19, our data show a very high of rate of anxiety and, especially, depression [ 24 , 25 , 26 ]. Of note, among our adolescents, 16.2% of the sample scored positive for suicidal or self-harm ideation.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the children and adolescents who contracted the viral infection, the data concerning the cognitive functioning and mental health are limited [ 24 , 25 , 26 , 27 , 28 ]. To the best of our knowledge, only two studies have evaluated cognitive problems in children and adolescents recovered from SARS-CoV-2 infection, and they did not explore the association with physical long-COVID complaints or psychological symptoms or included patients with a large age range [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have also shown depression, anxiety and other mood symptoms to be higher among postdischarge children with COVID versus healthy controls. 10,17…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have also shown depression, anxiety and other mood symptoms to be higher among postdischarge children with COVID versus healthy controls. 10,17 While our study did not include a control group of patients without COVID-19, our study did assess and report separately whether or not each of the sequelae were new diagnoses identified postdischarge (ie, not observed for the patient in the 5 months to 14-day period before the hospital admission). Even for the patients who had diagnoses for a given sequela both before and after the hospitalization, it is possible that COVID-19 exacerbated the severity or persistence of the symptom post-hospitalization; however, we are unable to assess this in medical claims data.…”
Section: Discussionmentioning
confidence: 99%
“…6 Children who were hospitalized for COVID-19 were also reported to have more severe depression, anxiety, and post-traumatic stress disorder symptoms than healthy controls. 7 Beyond its utility in a pandemic, caregivers would likely benefit from more age-appropriate support for their children in health care settings, as these can help reduce the stress and anxiety for the family during a new health care experience.…”
Section: Discussionmentioning
confidence: 99%